Analysis of Factors Associated with the Length of Hospital Stay Among Stroke Patients: A Scoping Review - Sudrisman Sudrisman; Bagoes Widjanarko; Antono Suryoputro (Indonesian Journal of Global Health Research, 2026)
Length of Stay (LOS) is a key determinant influencing inpatient care costs and serves as an important indicator of hospital service quality. The duration of hospitalization is affected by multiple factors. This study aims to identify the factors associated with the length of stay among patients with stroke. This research employed a scoping review approach using the databases Elsevier Scopus, Google Scholar, and Academia.edu. The review process consisted of the following stages: (1) identifying the research question, (2) identifying relevant articles, (3) screening articles, (4) data charting, (5) summarizing the findings, and (6) consultation. A total of 640 articles were initially selected based on title, abstract, content, and relevance to the inclusion criteria and objectives of this study. Following the screening process, next step was to analyze the 12 selected journals using the JBI Critical Appraisal tool. The inclusion criteria were full-text articles focusing on factors associated with the length of hospital stay in stroke patients, involving populations and samples of stroke patients aged over 18 years and/or their family members. This scoping review identified several factors associated with the length of hospital stay among stroke patients, including patient characteristics, comorbidities, stroke type, management strategies, complications, stroke symptoms, and smoking history, all of which may contribute to shorter hospitalization duration. The length of hospital stay among stroke patients may vary depending on multiple influencing factors. Further comprehensive studies are recommended to explore in greater depth the impact of these factors on hospitalization duration among stroke patients.